Advances in Heart Valve Biomechanics Valvular Physiology, Mechanobiology, and Bioengineering (Springer International Publishing, 2018)
This book covers the latest research development in heart valve biomechanics and bioengineering, with an emphasis on novel experimentation, computational simulation, and applications in heart valve bioengineering. The most current research accomplishments are covered in detail, including novel concepts in valvular viscoelasticity, fibril/molecular mechanisms of tissue behavior, fibril kinematics-based constitutive models, mechano-interaction of valvular interstitial and endothelial cells, biomechanical behavior of acellular valves and tissue engineered valves, novel bioreactor designs, biomechanics of transcatheter valves, and 3D heart valve printing. This is an ideal book for biomedical engineers, biomechanics, surgeons, clinicians, business managers in the biomedical industry, graduate and undergraduate students studying biomedical engineering, and medical students.